The Pathogenicity of Shewanella algae and Ability to Tolerate a Wide Range of Temperatures and Salinities - Shu-Ying Tseng; Po-Yu Liu; Yi-Hsuan Lee; Zong-Yen Wu; Chiu-Chen Huang; Ching-Chang Cheng; Kwong-Chung Tung (Canadian Journal of Infectious Diseases and Medical Microbiology)
Shewanella algae is a rod-shaped Gram-negative marine bacterium frequently found in nonhuman sources such as aquatic ecosystems and has been shown to be the pathogenic agent in various clinical cases due to the ingestion of raw seafood. The results of this study showed that S. algae was present in approximately one in four samples, including water and shellfish samples. Positive reactions (API systems) in S. algae strains were seen for gelatinase (gelatin); however, negative reactions were found for indole production (tryptophan). S. algae is adapted to a wide range of temperatures (4°C, 25°C, 37°C, and 42°C) and salinity. Temperature is a key parameter in the pathogenicity of S. algae as it appears to induce hemolysis at 25°C and 37°C. S. algae exhibits pathogenic characteristics at widely varying temperatures, which suggests that it may have the ability to adapt to climate change.